Exploring Undergraduate Students Perception of 4IR Digital Era at a Higher Education Institution in South Africa - Cele, Siphiwe; Bhana, Anrusha; Matli, Walter (Journal of Accounting Research, Organization and Economics, 2023)
Objective This study aims to explore undergraduate students perceptions and knowledge of 4IR in relation to their accounting curriculum and careers at HEIs in KwaZulu-Natal. The digital revolution is altering the way in which people and organizations work, as well as nearly every other aspect of human life. Furthermore, 4IR is re-writing society's fundamental rules, which highlights the need for this paper.Methodology This study used a census approach to gather quantitative data from one of South Africa's HEIs, via an online questionnaire link created with the Microsoft Forms application. The study was conducted online with a total population of 257 exit-level students from the Diploma in Accounting programme, the population that was targeted. The sample size was 172 out of 257 students, with a response rate of 66.9%.Results The findings indicated that students' knowledge of 4IR is limited, with only 56.4% of students having an understanding of what big data, artificial intelligence and the Internet of Things (IoT) are.Research limitations/implications There is a need to close the knowledge gap between Financial Accounting students knowledge of 4IR trends like big data, artificial intelligence (AI) and the Internet of Things (IoT) and curriculum content. The study's population was limited to exit-level students at one Higher Education Institution, hence the study's findings may not be generalizable to all HEIs.Novelty/Originality The studys novelty contributes to the growing body of research on how accounting technology can improve Financial Accounting education. The study provides an original perspective on the applicability of 4IR Accounting software systems and packages in a South African context, since most related studies were not conducted in South Africa. Furthermore, the study illustrates the importance of 4IR in the accounting curriculum.